(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the care burden, the current state of information technology (IT) use, and the need for IT applications among primary caregivers of cancer patients at the Oncology Centre, Thai Binh General Hospital in 2025. Subjects and methods: A cross-sectional descriptive study was conducted on 388 primary caregivers of cancer patients. Data were collected using a pre-structured questionnaire. Care burden was assessed using the ZBI-12 scale; the need for an IT application was measured using a 5-point Likert scale. Data were analysed using descriptive statistics. Results: The majority of caregivers were female (67.3%), under 60 years old (67.3%), and had a high school education or higher (54.6%). 74.7% of primary caregiver had a financial burden exceeding 10% of their income, 58.5% provided care for 12 hours or more per day, and 61.9% cared for patients with stages III-IV disease. The average ZBI-12 score was 19.51 ± 9.40, with the highest burden being mental (9.15 ± 4.82 points), followed by social (6.33 ± 3.88 points) and physical (4.04 ± 2.23 points). The proportion of primary caregiver with a high burden was 48.5%. 67.3% had used IT, but the majority used it for less than 1 hour/week (78.5%). The need for IT applications was high, with 84% of caregivers in the “necessary” group. The most common use was searching for information about cancer (90.8%). The main barriers in the non-using group were lack of knowledge/skills (76.4%) and lack of equipment (62.2%). Conclusion: Primary caregiver indicates that cancer patients in this study have a relatively high care burden, especially in terms of mental health. The rate of IT use reached 67.3%, while 84% of primary caregiver needed an IT application at an essential level.